Advances in Nanofibre Research - Haghi, A. K. (Handbook Ser., 2011)
Nanofibres are defined as fibres with diameters on the order of 100 nanometres. They can be produced by interfacial polymerisation and electrospinning. Nanofibres are included in garments, insulation and in energy storage. They are also used in medical applications, which include drug and gene delivery, artificial blood vessels, artificial organs and medical facemasks. This book presents some fascinating phenomena associated with the remarkable features of nanofibres in electrospinning processes and new progress in applications of electrospun nanofibres. It also provides an overview of structu.